Endoscopic Adenoidectomy with Microdebrider - Somani, S. S. (Springer-Verlag, 2011)
To describe endoscopic power assisted adenoidectomy and review the experience with the procedure demonstrating its safety and efficacy. Prospective study of 44 patients aged between 7 to 15 years undergoing power assisted adenoidectomy between Jan 2004 and July 2006. Tertiary care private teaching hospital. Forty four consecutive children with adenoid hypertrophy undergoing power assisted adenoidectomy. Therapeutic endoscopic adenoidectomy using microdebrider. Operative time, blood loss, complications, completeness and depth of removal, surgeon’s satisfaction and recovery period. The average operative time was 12 min (range: 8–16 min) and average blood loss was 30 ml (range: 24–42 ml). Complete resection was possible under vision with few complications. The surgeon satisfaction was high and post-operative recovery good. Power assisted adenoidectomy is quick, precise and safe. There is good visualization during resection thus improving precision and ensuring complete removal of adenoid tissue.